Achieving Indonesian palm oil farm-to-table traceability through ISPO-RSPO harmonization - Samuel Pablo Pareira (Center for Indonesian Policy Studies (CIPS), 2023)
This paper highlights the overlap between private sector and the state in regulating the sustainability of palm oil industry in Indonesia through the presence of two different certification schemes: the voluntary, global market-driven Roundtable on Sustainable Palm Oil (RSPO) and the mandatory, state-driven Indonesian Sustainable Palm Oil (ISPO). Increasing demand from global consumers for proof of sustainability in the industry requires comprehensive supply chain traceability. Since product tracing in each certification scheme covers different phases of the long palm oil supply chains, there is an opportunity to improve traceability and cover the entire supply chain by harmonizing the certifications to better accommodate both Indonesian regulations and the global norms that regulate palm oil sustainability. Comprehensive traceability would benefit all industry stakeholders (government, companies, smallholders, and NGOs) in ensuring the sustainability of Indonesian palm oil products in the global market.
Keywords: 330; Palmöl; Nachhaltigkeit; Standardisierung; Lieferkette; Transparenz; Regulierung; Indonesien; Welt